Estimation of the Critical Mass from Historical Values (1999 to 2019) of the Share Value in the Market Versus the Number of Users in Cinco Ecommerce - Guzmán Zabala, Juan Francisco
The aim of this work is to analyze the correlation between the critical mass of users on five e-commerce platforms listed on the Nasdaq and NYSE stock exchanges with global operations versus the monthly average share value. In order to comply with this, information on the number of monthly users and the value of the monthly action were collected and analyzed for a period of 20 years (1999 to 2019), to complete the missing data of some series of monthly active users. These were calculated from extreme data under the Makima method, which allowed the curves to be smoothed. As a result, the critical mass was calculated for the five selected e-commerces under thirteen sigmoidal functions and it was determined that the most suitable equation to estimate the critical mass is the 3-parameter sigmoid. Likewise, the Pearson correlation coefficient was calculated for the two variables (Number of users versus the value of the action) where a strong positive average correlation (0.86) was evident between them. Additionally, it was concluded that Walmart and The Home Depot, which were arised in the offline world, reached their critical mass in average at 11.7 years or 107,202,486 user. On the contrary, platforms that started online such as Amazon and eBay managed to reach critical mass on average at 25.2 years or 420,918,451 active users. Finally, it is concluded that critical mass is a key indicator that the digital entrepreneur can use to establish business strategies and achieve market leadership.